Fetal Cardiac Doppler Signal Processing Techniques: Challenges and Future Research Directions - Alnuaimi, Saeed Abdulrahman; Jimaa, Shihab; Khandoker, Ahsan H. (Frontiers in Bioengineering and Biotechnology, 2017)
The fetal Doppler ultrasound signal is commonly used for monitoring fetal heart rate, can also be used for identifying the event timings of fetal cardiac valve motions. In early-stage fetuses, the detected Doppler signal suffers from noise and signal loss due to the fetal movements and changing fetal location during the measurement procedure. The fetal cardiac intervals, which can be estimated by measuring the fetal cardiac event timings, are the most important markers of fetal development and well-being. To advance DUS-based fetal monitoring methods, several powerful and well-advanced signal processing and machine-learning methods have recently been developed. This review paper provides an overview about the existing techniques used in fetal cardiac activity monitoring and a comprehensive survey on fetal cardiac Doppler signal processing frameworks. The review is structured with a focus on their shortcomings and advantages, which helps in understanding fetal Doppler cardiogram signal processing methods and the related Doppler signal analysis procedures by providing valuable clinical information. Finally, a set of recommendations are suggested for future research directions and the use of fetal cardiac Doppler signal analysis, processing, and modeling to address the underlying challenges.